Rhizobial Volatiles: Potential New Players in the Complex Interkingdom Signaling With Legumes - Soto, María J.; López-Lara, Isabel M.; Geiger, Otto; Romero-Puertas, María C.; van Dillewijn, Pieter (Frontiers in Plant Science, 2021)
Bacteria release a wide range of volatile compounds that play important roles in intermicrobial and interkingdom communication. Volatile metabolites emitted by rhizobacteria can promote plant growth and increase plant resistance to both biotic and abiotic stresses. Rhizobia establish beneficial nitrogen-fixing symbiosis with legume plants in a process starting with a chemical dialog in the rhizosphere involving various diffusible compounds. Despite being one of the most studied plant-interacting microorganisms, very little is known about volatile compounds produced by rhizobia and their biological/ecological role. Evidence indicates that plants can perceive and respond to volatiles emitted by rhizobia. In this perspective, we present recent data that open the possibility that rhizobial volatile compounds have a role in symbiotic interactions with legumes and discuss future directions that could shed light onto this area of investigation.